The synthesis of analogues and bioisosteres of the acetylcholinesterase inhibitor donepezil in an attempt to identify novel anti-Alzheimer’s agents - Riley, Darren Lyall (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2020.